Analytical Methods for Toxics Determination - Locatelli, Marcello; Melucci, Dora; Locatelli, Clinio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The purpose of this volume is to show how in this area the technology, creativity and inventiveness are the basis of new and encouraging results not only in the environmental field but also in the monitoring of xenobiotics of organic and inorganic origin in complex matrices. The final objective will always be on determining the fundamental parameters of interest to set up an analytical procedure, such as precision and trueness (that together give accuracy), the limits of detection and quantification, selectivity, and especially sensitivity, or attempting to increase this